Palace of Horticulture (Pacific Novelty Co.)
On verso: A Cuban Palm Grove is a popular feature of the display in this beautiful palace, which covers an area of over five acres. The building is constructed almost entirely of glass and was designed by Bakewell & Brown, San Francisco.